PTH-113 Health-Related Quality of Life, Psychological Well-Being and Socioeconomic Impact in Patients with Cirrhosis and Their Caregivers. (17th August 2016) - Vadera, S; Greenslade, L; Morgan, MY
Abstract : Introduction: The psychological, social and economic consequences of a diagnosis of cirrhosis, for both patients and their families/friends, are not routinely assessed in the UK. The aim of this study was to assess Health-related Quality of Life (HRQoL), psychological well-being and socioeconomic burden in a random sample of patients with cirrhosis and their caregivers. Methods: The patient population comprised 51 patients with cirrhosis (38 men: 13 women; mean age 55 [21–87] yr) with no evidence of fluid retention utilising hospital inpatient/outpatient facilities and 15 patients (nine men: six women; mean age 60 [36–82] yr) attending the day-ward for large volume paracentesis (LVP). HRQoL was assessed using the generic EQ-5D questionnaire. The frequency of anxiety and depression was assessed using the Beck Anxiety ( BAI ) and Depression ( BDI ) inventories. The impact on employment and disease–related costs were assessed using an adapted financial questionnaire. 1 Caregivers' burden was assessed in 20 relatives/friends using the Perceived Caregivers Burden Scale and the Zarit Burden Interview . All patients/caregivers were interviewed to obtain additional information on psychosocial and general well-being. A control population of 52 individuals (28 men: 24 women; mean age 49 [26–68] yr) was also included. Results: HRQoL was significantly impacted in both the general patients with cirrhosis and in those undergoing LVP, compared to controls ( EQ-5D: 0.51±0.32 and 0.52±0.18 vs . 0.92±0.11; p < 0.001). The frequency of anxiety and depression was also significantly increased in the general patients with cirrhosis ( BAI 18.9±15.9: BDI 17.6±12.7; p < 0.001) and those undergoing LVP ( BAI 17.1±11.0: BDI 15.6±7.4; p < 0.001), compared with controls ( BAI 4.3±4.7: BDI 4.5±4.5; p < 0.001). Two-thirds of the general patients with cirrhosis and 100% of those undergoing LVP were unemployed; 50% considered their diagnosis had impacted on their employment status. The majority of patients were financially impacted, with direct out-of-pocket expenses, e.g. for hospital transport costs, of £350-£1500 since diagnosis. Approximately 15% of caregivers reported moderate anxiety while 5% reported moderate depression. The majority of caregivers were assessed as having a moderate degree of burden. Conclusion: Patients with cirrhosis have poor HRQoL and are often depressed and anxious; in addition they frequently have undisclosed socioeconomic difficulties. Caregivers are also detrimentally affected. Attention needs to be paid to the holistic needs of patients and careers, particularly in relation to their psychosocial and financial well-being. Reference: 1 Bajaj JS, et al. Am J Gastroenterol 2011;106 :1646–53. Disclosure of Interest: None Declared